2019
DOI: 10.3390/cells8121493
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Exacerbates the Transcriptional Profile of Hypoxia, Oxidative Stress and Inflammation in Rats with Adjuvant-Induced Arthritis

Abstract: Physical exercise (PE) is recommended for Rheumatoid Arthritis (RA), but the molecular and biological mechanisms that impact the inflammatory process and joint destruction in RA remain unknown. The objective of this study was to evaluate the effect of PE on the histological and transcriptional changes in the joints of adjuvant-induced arthritis (AIA) rat model. AIA rats were subjected to PE on a treadmill for eight weeks. The joints were subjected to histological and microarray analysis. The differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…17,18 Especially, studies have shown that embelin plays an important anti-inflammatory role by attenuating a variety of acute and chronic inflammation in the development of a variety of metabolic diseases. [19][20][21] Based on the perspective of embelin-induced antiinflammation and antioxidant effect, we were evaluated fabricating the embelin-loaded chitosan nanoparticles (CSembelin NPs) for immunopharmacological efficacy against adjuvant-induced arthritis (AIA) in rats and its relevant effects on immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Especially, studies have shown that embelin plays an important anti-inflammatory role by attenuating a variety of acute and chronic inflammation in the development of a variety of metabolic diseases. [19][20][21] Based on the perspective of embelin-induced antiinflammation and antioxidant effect, we were evaluated fabricating the embelin-loaded chitosan nanoparticles (CSembelin NPs) for immunopharmacological efficacy against adjuvant-induced arthritis (AIA) in rats and its relevant effects on immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Embelin, a main active constituent in the fruits of Embelia ribes Burm, has been approved by the United States Food and Drug Administration (US FDA), an administration for addressing the biochemical effects, such as antitumor, anti‐inflammatory, analgesic, antidiabetic, and antioxidant effects . Especially, studies have shown that embelin plays an important anti‐inflammatory role by attenuating a variety of acute and chronic inflammation in the development of a variety of metabolic diseases . Based on the perspective of embelin‐induced anti‐inflammation and antioxidant effect, we were evaluated fabricating the embelin‐loaded chitosan nanoparticles (CS‐embelin NPs) for immunopharmacological efficacy against adjuvant‐induced arthritis (AIA) in rats and its relevant effects on immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise induces increased expression of IL‐6, IL‐10, and IL‐15 and inhibits TNF‐α expression, possibly delaying the onset and progression of arthritis 63 . However, physical training can also negatively affect RA, depending on the training overload in direct correlation with the degree of mechanical stress and mediators of local inflammation, exacerbating RA‐related joint dysfunction 64 . Thus, the application of different physical training protocols likely induces different inflammatory parameters in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Yokoyama et al previously reported that a single-nucleotide polymorphism (SNP) in IPMK, which is associated with decreased expression of IPMK, was detected in samples from tissues of Alzheimer’s disease and immune-mediated diseases including RA, suggesting that IPMK is a risk factor for chronic inflammatory diseases (Yokoyama et al 2016 ). Furthermore, a recent study reported that the IPMK expression levels in an adjuvant-induced arthritis rat model were lower after exercise-induced physical stress (González-Chávez et al 2019 ). Taken together, the above-described evidence and our in vivo findings indicate that myeloid IPMK promotes RA resolution and is therefore a key molecular target with important clinical implications for RA treatment.…”
Section: Discussionmentioning
confidence: 99%